Embellished hollow spherical catalyst boosting activity and durability for oxygen reduction reaction. (September 2018) - Xu, Pan; Zhang, Jing; Jiang, Gaopeng; Hassan, Fathy; Choi, Ja-Yeon; Fu, Xiaogang; Zamani, Pouyan; Yang, Lijun; Banham, Dustin; Ye, Siyu; Chen, Zhongwei
Abstract: Transition metals hybridized to heteroatom doped carbon material can be regarded as the most promising non-noble candidate for boosting the sluggish kinetics of oxygen reduction reaction (ORR). However, it has always been a challenge to vastly boost the activity, and simultaneously retain a favorable structure from the supporting material. Herein, we prepared a high surface area hollow spherical carbon as a supporting material, and employed aminothiophenol (ATI) and poly-aminothiophenol (PATI) as heteroatom precursors to synthesize nitrogen and sulfur co-doped catalysts, i.e. HCS-A and HCS-PA, respectively. The two catalysts possessed chemically similar surface composition, and nearly identical chemical states for each element. However, only HCS-A was able to vastly inherit both morphological advantage and high surface area from the carbon support. In further half-cell electrochemical testing, HCS-A performed better ORR activities and higher selectivity toward 4 electron pathway than HCS-PA in both acidic and alkaline media. Moreover, HCS-A was proven to have excellent durability in half-cell testing, methanol tolerance as well as outstanding peak power density in both fuel cells and zinc-air batteries. This work not only indicates the promising performances of HCS-A, but more importantly offers a new viewpoint on the selection of heteroatom precursor to retain a favorable structure. Graphical abstract: Embellished hollow carbon spherical NPM catalyst (i.e. HCS-A) was synthesized to boost oxygen reduction reaction in both acidic and alkline media. The resultant catalyst shows excellent activity and durability. fx1 Highlights: Monomer and polymer was compared to elucidate the selection of nitrogen precursor; Longest half-cell durability to date was achieved in alkline medium; One of the highest peak power density was achieved in ambient zinc-air battery.